Identifikasi Faktor Utama Penghambat Pengembangan Bisnis Daring bagi Umkm Menuju Indonesia Ekonomi Digital - Marwan Setiawan; Jumisar; Seno Aji; Anita Wijayanti (LPPM Universitas Adiwangsa Jambi, 2021)
The development of the internet has radically changed business. The internet influences the development of technology, information, and communication. Information, communication, and technology have now been built based on big data/analytics, cloud, mobile and social business. This development is the basis of the 4.0 industrial revolution. The Government of the Republic of Indonesia is quite adaptive in facing the 4.0 industrial revolution with the development of the Road Map for Industry 4.0, a blueprint for the development of digital industry in Indonesia. Indonesia Digital Economy has become a vision of business development in Indonesia. The Indonesian government realizes that 70% of companies in Indonesia are micro, small and medium enterprises (SMEs) so that the Indonesian government has determined the backbone of Indonesia's Digital Economy success is SMEs. Online business is one of the effective strategies for accelerating SMEs to Indonesia Digital Economy. The purpose of this study is to determine the factors of barrier development online business by SMEs in Indonesia. This study shows 1) online business with company discrepancies, 2) online business is unsafe and high-cost and 3) online business implementation requires the right model for SMEs to be barrier factor for the online business development.